Factors affecting the relapse of maxilla and soft tissues of nose, upper lip and velopharyngeal structures after maxillary advancement in cleft patients. - Sirada Chaisiri; Raweewan Arayasantiparb; Kiatanant Boonsiriseth (PLoS ONE)
The objectives of this study were to find the factors affecting the relapses after maxillary advancement in cleft patients. This retrospective study included 25 cleft patients. The serial lateral cephalograms were used for the evaluation of the maxilla and the soft tissue relapses in 1-year post-operative period. The skeletal relapse rate correlated with the amount of skeletal movement only in horizontal direction (r = 0.483, p = 0.015). The patients with significant skeletal relapse did not have different amount of soft tissue relapses when compared to the patients without significant skeletal relapse, except for the A' point. Relapses of the soft tissue parameters of the upper lip and nose were correlated with the upper incisor tip position horizontally and vertically. When comparing the patients who underwent maxillary distraction (DO) with the patients who underwent conventional orthognathic surgery (CO), the DO group had greater NLA relapse and increase of pharyngeal depth than the CO group.